2015
DOI: 10.1109/toh.2015.2471300
|View full text |Cite
|
Sign up to set email alerts
|

Designing Haptic Assistive Technology for Individuals Who Are Blind or Visually Impaired

Abstract: This paper considers issues relevant for the design and use of haptic technology for assistive devices for individuals who are blind or visually impaired in some of the major areas of importance: Braille reading, tactile graphics, orientation and mobility. We show that there is a wealth of behavioral research that is highly applicable to assistive technology design. In a few cases, conclusions from behavioral experiments have been directly applied to design with positive results. Differences in brain organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 107 publications
0
24
0
2
Order By: Relevance
“…This controllability leads to the use of electrotactile stimulation as an alternative data channel to provide its user with information normally communicated through a different sense [1, 2]. Applications of sensory substitution include sensory prostheses for persons with serious visual [3-6], auditory [7, 8], and balance [9] impairments, as well as for those who have lost tactile sensation on some cutaneous loci (e.g. insensate hand or feet) due to traumatic nerve injury or disease [10], for feedback during advanced robotic surgical techniques [11], and potentially for virtual environment applications [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…This controllability leads to the use of electrotactile stimulation as an alternative data channel to provide its user with information normally communicated through a different sense [1, 2]. Applications of sensory substitution include sensory prostheses for persons with serious visual [3-6], auditory [7, 8], and balance [9] impairments, as well as for those who have lost tactile sensation on some cutaneous loci (e.g. insensate hand or feet) due to traumatic nerve injury or disease [10], for feedback during advanced robotic surgical techniques [11], and potentially for virtual environment applications [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the white cane can be used to detect obstacles in a short time through intuitive contact while the shoe-type walking assistive device needs a relatively long time to provide information about the obstacles identified by sensor signals. (13) Accordingly, the results of this study showed that the overall required time was shorter for the white cane than for the shoe-type walking assistive device in the small box area. However, the decrease in the required time over three trials was larger when walking with the shoe-type walking assistive device than with the white cane.…”
Section: Discussionmentioning
confidence: 68%
“…Kenneth 早在 1987 年提出了每种感官的信息容量参考等级:手指触觉 10 2 bits/s,听觉 10 4 bits/s, 视觉 10 6 bits/s [11] 。同时,大量的实验和生活经验表明,视觉受损人群的触觉和听觉优于健全人 [12] 。因 为人脑感觉皮层具有可塑性,盲人的触觉皮层和听觉皮层代谢活动增加,使盲人的触听觉更敏锐。 这说明针对盲人群体,触听觉虽然没有健全人的视觉信息容量大,但也拥有足够的认知交互空间的 潜力。 针对盲人的触觉交互,O'Modhrain 等 [13] 研究者们本身作为盲人,通过切身和周围盲人群体的触 觉认知体会,总结了目前触觉界面(Haptics)和触觉辅助设备,并分析了可触的、震动的、触觉交互 的辅助设备的优势及劣势。Pawluk 等将触觉交互概括为以下 4 个场景:布莱尔盲文(Braille)阅读、 触觉图形、触觉导航以及触觉移动应用 [14] 。而针对最近似视觉的触觉图形图像方面,Vidal-Verdu 和 Hafez 从硬件技术方面归纳分析了面向盲人的图形化触觉显示器,以及它们的使用体验 [15] 。综上 , 针对盲人而言,触觉认知与交互是理解可视化信息的最佳方式,尤其是大尺寸触觉点阵屏幕的引 入,使一般的图形图像转换为触觉形式,比如触点凸起、震动、电刺激等形式,易于盲人理解。 相对触觉,听觉和听觉交互分为两类:环境音和语音。环境音更多的作为盲人感知理解环境的 方式,感知范围广于触觉。Lumbreras 和 Sanchez 利用 3D 环绕声音使盲人感知,并用于盲人学习和 娱乐 [16] 。语音作为盲人获取信息最重要的方式,其交互性在目前也广泛被盲人接受并使用。2010 年 苹果公司的 Siri [7] 语音助手引领了互联网时代智能终端的语音交互,类似的语音助手应用还有微软的 Cortana…”
Section: 盲人触听觉多通道交互模型unclassified